Optimized synthesis of the melatonin metabolite N(1)-acetyl-N(2)-formyl-5-methoxykynuramine (AFMK) - Ximenes, Valdecir Farias [UNESP] (Wiley-Blackwell, 2008)
N(1)-acetyl-N(2)-formyl-5-methoxykynuramine (AFMK) is the product of oxidative pyrrole ring cleavage of melatonin. AFMK and its deformylated derivative N(1)-acetyl-5-methoxykynuramine (AMK) are compounds for which there are increasing demands because of their antioxidant, immunomodulatory and anti-inflammatory properties. Here, we sought to determine the best reaction conditions for preparation of AFMK using chlorpromazine (CPZ) as a co-catalyst in the peroxidase-mediated oxidation of melatonin. The parameters studied were pH, identity and concentration of buffers, hydrogen peroxide (H(2)O(2)) and CPZ concentrations and the presence or absence of dissolved molecular oxygen in the reaction medium. The rate and efficiency of AFMK production were compared with a noncatalyzed method which uses a high concentration of H(2)O(2). We found that by using CPZ and bubbling molecular oxygen during the course of the reaction, the yield of AFMK was significantly increased (about 60%) and the reaction time decreased (about 30 min), as compared with the noncatalyzed reaction (yield 32% and reaction time 4 hr). Based on these data, we suggest that this could be a new, easily performed and efficient route for AFMK preparation. Additionally, we provide evidence that a radical chain reaction could be responsible for the formation of AFMK.
Keywords: chlorpromazine; horseradish peroxidase; melatonin; N(1)-acetyl-N(2)-formyl-5-methoxykynuramine